ADHD prevalence in the psychiatric population. (1st June 2022) - Gerhand, Sina; Saville, Christopher W. N.
Abstract: Objective: This article presents a systematic literature review of the prevalence of Attention Deficit Hyperactivity Disorder (ADHD) in the adult psychiatric population. Methods: Three databases were searched using keywords relating to ADHD and psychiatric disorders. Fifteen studies published before May 2020 met inclusion criteria. Results: Prevalence rates ranged from 6.9 to 38.75%. There was considerable heterogeneity with regards to the assessment methods of ADHD and comorbidities, the sampling as well as inclusion and exclusion of psychiatric comorbidities. Research concluded that ADHD is underdiagnosed in this population. Gender ratios also varied between 1.8:1 and 1:2.5 (male:female). Conclusions: All ADHD prevalence rates for the psychiatric population were considerably higher than the 2.8% estimated for the general adult population. ADHD should be kept in mind for psychiatric patients to ensure accurate diagnosis and optimal treatment options. Key Points: ADHD is considerably underdiagnosed in the psychiatric population Gender ratios between 1.8:1 and 1:2.5 (male:female) reported in research More research is needed to ascertain if the use of ADHD screening instruments would improve the recognition and treatment of adult ADHD in the psychiatric population.